Work patterns in the professional life-cycle - Joseph A. Raelin (Journal of Occupational Psychology, 1985)
A discriminant analysis was performed on a sample (n = 114) of salaried professionals to distinguish work patterns among three age groups corresponding to early, middle and late career stages. Three distinct profiles were generated by the two significant discriminant functions which emerged. The three career stage groups were given identifying labels: `finding a niche', `digging in' and `entrenched'. The findings support a life-cycle hypothesis of ageing and work patterns, although there is some substantiation for the cohort and ageing hypotheses in the literature. Scenarios for each of the three career stages are provided along with implications for improving the management of age-specific professional human resources.
Keywords: L84; J44; J24; J28; O15; M12; M53; 330; Professional work; Managing professionals; Age and work; Work tenure; Job satisfaction; Deviance; Self-esteem; Discriminant analysis